Application of Learning Management Using Non-test Instrument to Improve the Quality of Education - Winarno, Winarno; Muhtadi, Yudi; Aldiya, Much Alvin (APTISI Transactions on Management (ATM), 2019)
The quality of education is influenced by many factors in it. These factors include students, school managers, educational environment, quality of education, curriculum, learning materials and so on. A good learning system will produce good quality education, then a good assessment system will encourage teachers to determine good teaching strategies and motivate students to learn better. In connection with that, the learning needs of teachers who are not only able to teach well, but also able to evaluate well. Evaluation is not only based on the assessment of learning outcomes, but also an assessment of input, output and the quality of the learning itself. Research instruments can be interpreted as a tool for collecting research data. Basically the research instrument consisted of tests and non-tests. Non-test instruments are testing instruments in addition to learning achievement tests. Assessment tools that can be used include observation or observation sheets (such as diaries, portfolios, life skills), attitude test instruments, interests, interview techniques, questionnaires, sociometry, case studies, and so on. In the development of non-test instruments that need to be considered are the steps to develop the instrument, the preparation of the non-test instrument grid, and the rules for writing instrument items. In this study will be explained in detail about the preparation of non-test instruments, scoring techniques and also the rules of writing a portfolio.